El concepto de “revolución” en José Martí - Mora Rodríguez, Arnoldo (2007)
This essay searches to situate in the historical context al the end of the century the political, philosophical and literary contribution of José Martí. With him ends a century and also creates an integral historical project for all the people of our America for the new century.